2018
DOI: 10.3892/or.2018.6618
|View full text |Cite
|
Sign up to set email alerts
|

Impact of RNA‑binding motif 3 expression on the whole transcriptome of prostate cancer cells: An RNA sequencing study

Abstract: RNA‑binding motif 3 (RBM3) is a cold‑shock protein that has been previously shown to attenuate cancer stem cell‑like features in prostate cancer (PCa) cells. However, the mechanism underlying RBM3 regulation in PCa cells is largely unknown. The present study investigated the impact of RBM3 expression on the whole transcriptome of PCa cells using high‑throughput RNA sequencing (RNA‑seq). Differentially expressed genes (DEGs) that were identified through RNA‑seq were applied to Gene Ontology (GO), pathway analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…As a stress-response protein, RBM3 also has RNA-binding properties which play a crucial role in determining the fate of cancer cells in the tumor microenvironment [ 42 44 ]. We have previously shown that the expression of RBM3 was significantly decreased in cells that survived stressful environments, such as high temperature, chemotherapy conditions or a soft agar environment, favoring the enhanced stemness feature of surviving cells by inducing cell quiescence [ 12 , 45 , 46 ]. In the present study, we similarly observed that interaction of PCa cells with the bone microenvironment reduced the expression of RBM3, and this potentially “permitted” the activation of Wnt β -catenin signaling which is critically important for bone metastasis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…As a stress-response protein, RBM3 also has RNA-binding properties which play a crucial role in determining the fate of cancer cells in the tumor microenvironment [ 42 44 ]. We have previously shown that the expression of RBM3 was significantly decreased in cells that survived stressful environments, such as high temperature, chemotherapy conditions or a soft agar environment, favoring the enhanced stemness feature of surviving cells by inducing cell quiescence [ 12 , 45 , 46 ]. In the present study, we similarly observed that interaction of PCa cells with the bone microenvironment reduced the expression of RBM3, and this potentially “permitted” the activation of Wnt β -catenin signaling which is critically important for bone metastasis of PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that H3 acetylation of the transcription intermediary factor (TIF) family of proteins is important for cell proliferation in a number of different cancers (26)(27)(28)(29). We hypothesized that KAT2B enhanced H3K14 acetylation of TIF proteins, which then acted as transcriptional activators enhancing downstream gene expression, resulting in improved YAP stability and promoting NPC proliferation.…”
Section: Binding Of Tif1a To H3k14ac Is Required For Afap1-as1-drivenmentioning
confidence: 99%
“…RBM3 inhibits CD44v8‐v10 splicing to attenuate the stem cell‐like character of prostate cancer cells (Dong et al, 2018; Zeng et al, 2013). Meanwhile, RBM3 inhibits glycogen synthase kinase‐3β, activity and stimulates the Wnt/β‐catenin pathway, thereby enhancing the stem cell characteristics of colorectal cancer cells (Venugopal et al, 2016).…”
Section: Rbm3 and Its Multiple Functionsmentioning
confidence: 99%